KARAKTERISASI DAN OPTIMASI MEDIA PRODUKSIAMILASE , DARI Aspergilus niger DAN Aspergilus clavatus - Elidar Naiola (BERITA BIOLOGI, 2002)
Six fungi isolates belong to Aspergillus spp were isolated from various samples and their ability to produce amylase has been tested. It was founded that all isolate shown the amylolytic activities which shown the clear zone areas after pouring with iodium solution. Two isolates which name Aspergillus niger (ISO 482) dan A. clavatus (ISO 468) to be the most active compare to another. The amylase activity of two isolate was studied in media contain rice and rice brain as a carbohydrate sources. Based on lower cost and easy to reach rice brain (local waste agriculture product) were choose as the alternative media to produce enzyme amylase from Aspergillus niger (ISO 482). The activities 2 of enzyme obtain was 54,14 x 10  U/ml (one unit activity is define as micromoles of glucose produce per ml per minute). The optimiation was done at room temperature for 7 days. The result showed the activity of enzyme increase during the fermentation process, at the first 2 2 day activity was 18,77 x 10 U/ml and reached the maximum activity (91,64 x 10 U/ml) after 3 days. The optimum temperature for enzyme reaction was 40 - 50 °C, optimum pH was (pH 5.0 - 7.0) and enzyme was relatively stable under such conditions.